Study and Application of Heat Self-generated gases Flooding for Enhance Heavy Oil Recovery with Low-frequency High-power Harmonic Wave. Issue 1 (February 2021) - Guowei, Qin; Yanzhao, Zheng; Rongbo, Jin; Jing, Wang; Beilei, Zhang; Qiao, Wang; Mei, Wu
Abstract: Heat self-generated gases flooding with low-frequency high-power harmonic wave(LFHPHW) is a new technology combining of LFHPHW enhanced oil recovery, steam flooding, and gas flooding and so on. Its main mechanism is to improve the fluidity and reduce heavy oil viscosity and oil-water interfacial tension with self-generated gases (CO2, NH3, etc.). They can be further reduced by synergism effect with LFHPHW, which can improve the heavy oil fluidity and displacement efficiency to enhance heavy oil recovery. The results of this new technology show that it has many advantages and can enhance heavy oil recovery(EHOR).